Peran Perceived Organizational Support terhadap Work Engagement pada Karyawan Outsourcing - Anggi Tri Lestari Purba; Adelin Australiati Saragih (MAN 4 Kota Pekanbaru, 2026)
The increasing use of outsourcing employees in organizations requires strong work engagement to support organizational success, which may be influenced by perceived organizational support. The study aims to assess the contribution of perceived organizational support to work engagement among outsourced employees. A quantitative approach was employed, with a total of 92 outsourced employees selected through total sampling. A simple linear regression approach was applied to analyze the data. The empirical findings indicate that perceived organizational support contributes 54.4% to work engagement. Therefore, companies need to strengthen supervisory support and justice, while continuing to pay attention to rewards and working conditions in order to enhance employees’ engagement to the organization.